Age and sex differences on anti-hyperglycemic medication exposure and risk of newly diagnosed multiple sclerosis in propensity score matched type 2 diabetics. Issue 10 (October 2022) - Branigan, Gregory L.; Torrandell-Haro, Georgina; Vitali, Francesca; Brinton, Roberta Diaz; Rodgers, Kathleen
Abstract: Background: The association between exposure to anti-hyperglycemic medications (A-HgM) for Type 2 Diabetes Mellitus (T2D) treatment and Multiple Sclerosis (MS) in T2D patients is unclear. Methods: This retrospective cohort analysis used the Mariner claims database. Patient records were surveyed for a diagnosis of MS starting 12 months after diagnosis of T2D. Patients were required to be actively enrolled in the Mariner claims records for six months prior and at least three years after the diagnosis of T2D without a history of previous neurodegenerative disease. Survival analysis was used to determine the association between A-HgM exposure and diagnosis of MS. A propensity score approach was used to minimize measured and unmeasured selection bias. The analyses were conducted between January 1st and April 28th, 2021. Findings: In T2D patients younger than 45, A-HgM exposure was associated with a reduced risk of developing MS (RR: 0.22, 95%CI: 0.17–0.29, p-value <0.001). In contrast, A-HgM exposure in patients older than 45 was associated with an increased risk of MS with women exhibiting greater risk (RR: 1.53, 95%CI: 1.39–1.69, p < 0.001) than men (RR: 1.17, 95%CI: 1.01–1.37, p = 0 · 04). Patients who developed MS had a higher incidence of baseline comorbidities. Mean follow-up was 6.2 years with a standard deviation of 1.8 years. Interpretation: In this study, A-HgM exposure in patients with T2D was associated with reduced risk of MS in patients younger than 45 whereas in patients older than 45, exposure to A-HgM was associated with an increased risk of newly diagnosed MS, particularly in women. Abstract : Multiple sclerosis; Type 2 diabetes, Informatics, Health claims, Risk.